Engineered fatty acid catabolism for fuel and chemical production. (December 2016) - Kim, Seohyoung; Cheong, Seokjung; Chou, Alexander; Gonzalez, Ramon
Graphical abstract: Highlights: Bio-based renewable chemical production is becoming increasingly important. Engineering of fatty acid catabolism enables microbial production of aliphatic and functionalized chemicals. Selective functionalization of fatty acid can be achieved through α-, β-, and ω-oxidation routes for fatty acid degradation. Engineered reversal the β-oxidation cycle is a promising carbon chain elongation platform. Abstract : Fatty acid oxidation pathways are attractive for metabolic engineering purposes due to their cyclic nature as well as their reactions that allow for the selective functionalization of alkyl chains. These characteristics allow for the production of various chemicals, such as alcohols, alkanes, ketones and hydroxyacids, in a wide range of carbon numbers. To this end, the α-, β-, and ω-oxidation pathways have been engineered for use in various hosts. Furthermore, the β-oxidation pathway has been engineered to operate in reverse, resulting in a promising carbon chain elongation platform. This review will describe the recent progress in metabolic engineering strategies for the production of chemicals through these fatty acid oxidation pathways.